THE EXPLORATION OF STUDENTS’ ATTITUDES TOWARDS BI/MULTILINGUALISM ACQUISITION: A CASE STUDY OF NON-ENGLISH MAJOR STUDENTS - Ria, Nita; Sari, Farnia; Budiyanto, Darmawan; Tridinanti, Gaya (English Community Journal, 2023)
Attitudes refer to the behavior of how people respond to their own language or are being taught. A qualitative research design with 27 students of Non-English Major at Private University. The collected data was questionnaire and in-depth interview. The data were analyzed using the percentage analysis and thematic analysis. The result indicates students’ attitudes towards L1, L2, L3, L4 etc. In opinion, L1 and L2 were still maintained and used in daily activities, whereas foreign languages such as L3 or L4 seem to get much more exposure through social media or formal domains. In the feeling aspect, the majority of students were excited to learn their languages that were implemented in the classroom due to challenging and fun. However, foreign language as their L3 or L4 was still distracted from learning in the classroom. In language use, L1 and L2 are used in the surrounding environment for communicating with their relatives, friends, and etc., L3 or L4 seems to be required for formal domain, social status and future career. Building on these results, techniques and strategies could be applied in the classroom and the parents could encourage their mother tongues to use in a certain place and keep on maintaining to encourage students’ attitudes.